Impact of metal-optical properties on surface-enhanced infrared absorption - Tzschoppe, Michael; Huck, Christian; Vogt, Jochen; Neubrech, Frank; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
Surface-enhanced infrared absorption (SEIRA) spectroscopy using resonant metallic nanostructures is increasingly attracting interest during the last decade. Nevertheless, the impact of the metals’ intrinsic properties on SEIRA is still little studied. We present an experimental work on this topic, examining the infrared-optical resonance spectra of linear nanoantennas made of five of the most common metals (gold, silver, copper, aluminum, and iron) with respect to the intrinsic and radiation damping. Highly material- and size-dependent ratios of the two damping contributions were found and discussed. Using layers of organic probe molecules, we obtained SEIRA enhancement factors for the different nanoantennas and experimentally verified the predicted relationship between the plasmonic damping mechanisms and the SEIRA enhancement. The multitude of our experimental data for the ratio between the intrinsic electronic damping and the radiation damping is compared with the measured SEIRA enhancement of the various nanoantennas and therefore deliver the proof that the best SEIRA enhancement is achieved when both damping mechanisms equally contribute. Furthermore, it is shown that for a given nanoantenna geometry, the red-shift away from the plasmonic extinction maximum is strongly dependent on material parameters.